2019
DOI: 10.1177/0192513x19842243
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothers and Non-grandmothers in the Polish Labor Market: The Role of Family Issues

Abstract: Drawing on the debates regarding work–family reconciliation in later life, we examine the extent to which the labor market position of grandmothers and nongrandmothers can be explained by their varied family situations. The data for this study comes from the Generations and Gender Survey for Poland and includes 5,999 women aged 45+ years. We use multinominal logistic regression models to explore the link between different family situations and labor market withdrawal into unemployment, sick/disability leave, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Moreover, the high rates of young working mothers who rely on their parents, and especially on their mothers, for child care mean that contemporary grandmothers still in formal employment outside the home are likely to combine work with the duties of caring for their own grandchildren (Meyer, 2014). In the past decade, as researchers have realized that many grandmothers are still employed in the workforce, attention has turned to the question of how grandparents, and not just working mothers, manage the combined load of work responsibilities and commitments to caring for grandchildren (Hochman & Lewin-Epstein, 2013; Lakomy & Kreidl, 2015; Meyer, 2014; Wilinska et al, 2019). These studies have yielded inconsistent conclusions regarding the correlations between a grandmother’s salaried employment and her role as a caregiver.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the high rates of young working mothers who rely on their parents, and especially on their mothers, for child care mean that contemporary grandmothers still in formal employment outside the home are likely to combine work with the duties of caring for their own grandchildren (Meyer, 2014). In the past decade, as researchers have realized that many grandmothers are still employed in the workforce, attention has turned to the question of how grandparents, and not just working mothers, manage the combined load of work responsibilities and commitments to caring for grandchildren (Hochman & Lewin-Epstein, 2013; Lakomy & Kreidl, 2015; Meyer, 2014; Wilinska et al, 2019). These studies have yielded inconsistent conclusions regarding the correlations between a grandmother’s salaried employment and her role as a caregiver.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The harm is not only financial but their leisure time and social lives also suffer due to these sacrifices. Wilinska and colleagues found that grandmothers have lower chances for being employed compared to women without grandchildren (Wilinska et al, 2019). Other studies, however, did not associate negative outcomes with the combining of work and caring for grandchildren (e.g., Silverstein & Marenco, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most prior studies that considered the association between grandparents' employment status and grandchild care did not distinguish between retired grandparents and those who do not work for other reasons (such as unemployment or illness) (Aassve et al, 2012 ; Danielsbacka and Tanskanen, 2012 ; Di Gessa et al, 2016 ; Železna, 2018 ; Wilińska et al, 2019 ; Zamarro, 2020 ). In addition, prior studies have almost exclusively used cross-sectional data and compared two different groups of individuals, that is, they have compared the grandchild care of working grandparents with that of non-working grandparents.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior studies on the association between grandparents' employment status and provision of grandchild care mostly used cross-sectional data and have shown that employed grandparents tend to provide less child care to their grandchildren compared to those grandparents out of the labor market (i.e., retired, unemployed, permanently sick etc.) (Aassve, Meroni & Pronzato, 2012;Danielsbacka & Tanskanen, 2012;Zamarro, 2020) and retired grandparents provide more child care help than grandparents who are not retired (Di Gessa et al, 2016;Wilińska et al, 2019;Zelezna, 2018).…”
Section: Grandparents' Employment Status and Grandchild Carementioning
confidence: 99%